Getting the dead to tell me what happened: Justice, Prosopopoeia, and Forensic Afterlives - Keenan, Thomas (Kronos: Southern African Histories, 2020)
It is one thing to make someone or something disappear, and another thing to make a disappearance itself disappear. The two often go hand in hand – an abduction or a murder removes someone from their world, and then the traces of that erasure are erased as well. (I say ‘often’ because there are exceptions: sometimes the forces of disappearance seek to amplify their power or generate obedience by promoting their capacity to make things and people go away.) In an ironic twist, though, it can also happen that projects designed to undo the first disappearance can themselves contribute to the disappearance of the disappearance. For instance, when forensic experts identify the remains of missing persons, or authorities claim that ‘closure’ has been brought to an otherwise unfinished chapter in history, it can seem as if the uncertainty and limbo of missing-ness has been definitively put to rest. The missing are no longer lost, but found; the lie is undone by the truth, the denial exposed.